The Effect of Intramuscular 17α-Hydroxyprogesterone in Women Screened for Shortened Cervical Length - Wood, S. Lindsay; Williams, Bria N.; Szychowski, Jeff M.; Owen, John (American Journal of Perinatology, 2020)
Objective This article assesses the effect of weekly intramuscular 17α-hydroxyprogesterone caproate (17P) on midtrimester cervical length (CL) in patients with prior spontaneous preterm birth.Study Design Retrospective cohort study of all singletons that underwent CL screening at a single institution from 2011 to 2016. The timing of 17P exposure was assessed. The primary outcome was shortest midtrimester CL. Secondary outcomes included gestational age at delivery, rate of short cervix, cerclage, preterm labor admission, and preterm premature rupture of the membranes (PROM). Multivariable regression analysis was used to model the relationship between 17P exposure and shortest CL, controlling for selected covariates.Results Of 409 women who underwent screening, 211 received and 198 did not receive 17P prior to the last CL. Rates of short cervix and cerclage were similar between groups. After adjusting for covariates, the shortest CL was significantly shorter in the 17P group. In a secondary analysis, those who received any 17P (n = 293) versus those who did not (n = 116) had higher rates of preterm PROM, preterm labor admission, and cerclage. After controlling for covariates, gestational age at delivery was significantly lower in those receiving 17P.Conclusion In high-risk patients undergoing CL screening for ultrasound-indicated cerclage, 17P did not prevent midtrimester cervical shortening or prolong gestation.
Keywords: cervical length screening; preterm birth; effect of progesterone; recurrent preterm birth prevention; cerclage